Effects of Acupuncture on the Recovery Outcomes of Stroke Survivors with Shoulder Pain: A Systematic Review - Chau, Janita Pak Chun; Lo, Suzanne Hoi Shan; Yu, Xingfeng; Choi, Kai Chow; Lau, Alexander Yuk Lun; Wu, Justin Che Yuen; Lee, Vivian Wing Yan; Cheung, William Hoi Ngai; Ching, Jessica Yuet Ling; Thompson, David R. (Frontiers in Neurology, 2018)
Background: Poststroke shoulder pain limits stroke survivors’ physical functioning, impairs their ability to perform daily activities, and compromises their quality of life. The use of acupuncture to manage shoulder pain after a stroke is believed to free the blockage of energy flow and produce analgesic effects, but the evidence is unclear. We therefore conducted a systematic review to summarize the current evidence on the effects of acupuncture on the recovery outcomes of stroke survivors with shoulder pain. Methods: Fourteen English and Chinese databases were searched for data from January 2009 to August 2017. The review included adult participants with a clinical diagnosis of ischemic or hemorrhagic stroke who had developed shoulder pain and had undergone conventional acupuncture, electro-acupuncture, fire needle acupuncture, or warm needle acupuncture. The participants in the comparison group received the usual stroke care only. Results: Twenty-nine randomized controlled trials were included. Most studies were assessed as having a substantial risk of bias. Moreover, due to the high heterogeneity of the acupuncture therapies examined, pooling the results in a meta-analysis was not appropriate. A narrative summary of the results is thus presented. The review showed that conventional acupuncture can be associated with benefits in reducing pain and edema and improving upper extremity function and physical function. The effects of conventional acupuncture on improving shoulder range of motion are in doubt because this outcome was only examined in two trials. Electro-acupuncture might be effective in reducing shoulder pain and improving upper extremity function, and conclusions on the effects of electro-acupuncture on edema, shoulder range of motion, and physical function cannot be drawn due to the limited number of eligible trials. The evidence to support the use of fire needle or warm needle acupuncture in stroke survivors with shoulder pain is also inconclusive due to the limited number of studies. Conclusions: Although most studies reviewed concluded that conventional and electro-acupuncture could be effective for management of shoulder pain after stroke, the very high potential for bias should be considered. Further work in this area is needed that employs standardized acupuncture treatment modalities, endpoint assessments, and blinding of treatments.